A balkáni "lőporos hordó" izzó kanóca : Bosznia-hercegovinai konfliktus-leltár a világháború előestéjén - Makkai, Béla (Közép-Európai Közlemények, 2014)
This study outlines how the AustroHungarian Monarchy, with emphasys on the international power constellation, went through the process of occupation of Bosnia and Hercegovina in 1878 to the later annexation in 1908. This process was characterized by internal difficulties which were imbued by different historical traditions, three cultures and four religions. It slowed the modernization efforts of the Kállay era. The author points out that the “civilianizing” misssion of the Monarchy got on well with the urge for colonial exploitation, fiercely criticized by the nationaly and socialy divided elite, also living with the possibilities of the limited constitution of 1910. Serbia, as the Piedmont of the South Slavic unification, was involved in the custom war with its imperial neighbour between 1906 and 1910 by the means of international propaganda, border provocation and support of secret organizations in order to achieve the separation of the two provinces. The issue had been further complicated by the great Croatian trialist reunification efforts, majorly supported by Archduke Franz Ferdinand. His personage was eliminated in 1914, by the Serbian Government through its terrorist organization Black Hand (Crna Ruka) endorsed by the Tsarist Empire Alliance. This is how the first gunshot in Sarajevo sparked the flame which led to the WWI.